2021
DOI: 10.1016/j.jmgm.2021.107970
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and structural basis for the differences in infectivity between the wild-type and mutant spike proteins of SARS-CoV-2 in the Mexican population

Abstract: SARS-CoV-2 is the causative agent of the ongoing viral pandemic of COVID-19. After the emergence of this virus, it became a global public health concern and quickly evolved into a pandemic. Mexico is currently in the third position in the number of deaths due to SARS-CoV-2. To date, there have been several lineages of SARS-CoV-2 worldwide; in the Mexican population, two variants of the spike protein (S-protein) are found, localized at H49Y and D614G, which have been related to increased infectivity with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Although the erection of the RBD is a prerequisite for ACE2 binding, the RBD is an independently folded domain and its erection has only a marginal impact on its overall conformation [17]. As a result, the binding affinity of the spike protein to the ACE2 was usually evaluated using the RBD rather than the spike trimer, although previous computational studies showed that certain mutations outside the SARS-CoV-2 spike RBD were capable of influencing an affinity to the ACE2 through altering the spike conformational dynamics [22,23]. Interestingly, multiple earlier experimental and simulation studies have collectively demonstrated that the SARS-CoV-2 RBD (RBD CoV2 ) has a higher ACE2-binding affinity than the SARS-CoV RBD (RBD CoV ) [16,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Although the erection of the RBD is a prerequisite for ACE2 binding, the RBD is an independently folded domain and its erection has only a marginal impact on its overall conformation [17]. As a result, the binding affinity of the spike protein to the ACE2 was usually evaluated using the RBD rather than the spike trimer, although previous computational studies showed that certain mutations outside the SARS-CoV-2 spike RBD were capable of influencing an affinity to the ACE2 through altering the spike conformational dynamics [22,23]. Interestingly, multiple earlier experimental and simulation studies have collectively demonstrated that the SARS-CoV-2 RBD (RBD CoV2 ) has a higher ACE2-binding affinity than the SARS-CoV RBD (RBD CoV ) [16,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%